2006
DOI: 10.1590/s1517-86922006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre limiar anaeróbio determinado por variáveis ventilatórias e pela resposta do lactato sanguíneo em ciclistas

Abstract: Muitas investigações têm demonstrado que a coincidência entre os limiares ventilatórios e os limiares que se utilizam da resposta do lactato nem sempre ocorre, sugerindo que não existe relação entre causa e efeito entre os fenômenos. Dessa forma, o presente estudo teve como objetivos comparar e correlacionar os valores de consumo de oxigênio (VO2), potência (W) e freqüência cardíaca (FC) obtidos por protocolos de determinação do limiar ventilatório (LV) e limiar anaeróbio individual (IAT). A amostra foi consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
5
0
4
Order By: Relevance
“…During this test, physical fitness is evaluated by determining parameters of physiological thresholds, such as maximum oxygen uptake (VO 2 max), or by measuring blood lactate and estimated VO 2 max [9]. VO 2 max corresponds to the moment when the maximum capacity to deliver oxygen for glucose oxidation is achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this test, physical fitness is evaluated by determining parameters of physiological thresholds, such as maximum oxygen uptake (VO 2 max), or by measuring blood lactate and estimated VO 2 max [9]. VO 2 max corresponds to the moment when the maximum capacity to deliver oxygen for glucose oxidation is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of physical effort after reaching the LT leads to loss of the oxidative capacity of the muscle, shifting the metabolism to anaerobic, which leads to lactate accumulation, faster fatigue, release of catecholamine and increase blood glucose levels [10, 11]. Physical fitness evaluation through blood lactate measurement, especially using portable devices, can easily be performed in field tests, besides being accessible to most physical evaluation professionals due to its relatively low cost [9]. In healthy subjects, measurement of blood lactate during exercise has been used to evaluate aerobic capacity and to determine the ideal intensity of exercise [12].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease or insufficient elevation of this variable indicates ischemic disease, or morphological alterations in the cardiovascular system. 28,29 One of the classic studies on the behavior of heart rate during progressive physical exercise performed in healthy men during a ergometer test on cycle ergometer showed that heart rate values increased during LA compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Antes da avaliação, as voluntárias foram submetidas aos seguintes procedimentos em relação à escala de BORG 6 : foram apresentadas a cada item da escala de Borg (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Percepção Subjetiva De Esforço (Pse)unclassified